Infiltration in forestry, livestock and agricultural soils, analysis for water management in Málaga Santander - Colombia - Hernández Saldaña, Lady Vanessa; Meneses Padilla, Diego Alirio; Ruiz-Ochoa, Mauricio Andrés; Oviedo-Celis, Ricardo Andrés (Bosque (Valdivia), 2025)
The soil and the vegetation cover it supports are an important source of ecosystem goods and services; however, the unsustainable use and exploitation of these natural resources cause negative impacts that affect processes such as infiltration. The study analyzes the infiltration capacity in four typical land uses of the rural area in the municipality of Málaga Santander - Colombia. The composition and structure of the flora in a forest, forest plantation, agroforestry system and pasture were characterized, the infiltration capacity was measured by the double ring method, in 15 replicates per soil use, where soil samples were also extracted at 0.30 m depth for physical properties analysis. The quantification of infiltration capacity was carried out by the Kostiakov model, field data were subjected to ANOVA, Tukey (P<0.05) and Pearson correlation tests. The results showed differences in composition and structure of the flora, and the soils are characterized by a bulk density, total porosity and moisture not similar. The infiltration rate showed no differences between forest and forest plantation. Basic infiltration was directly correlated with bulk density, total porosity and humidity. It was concluded that soil use and some physical properties influence the infiltration capacity, information that can help communities in rural sectors of the Andes of Colombia to define actions for the integrated management of water resources in their territories, based on the knowledge of the vegetation cover that they implement.